(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In a restricted temperature range, the development and stage-specific mortality of Oulema duftschmidi (Redtenbacher) eggs, larvae and pupae, are compared to the responses of corresponding O. melanopus (L.) and O. gallaeciana (Heyden) life stages. The developmental rates are similar on the egg stage, while O. duftschmidi larvae and pupae developed slower than the corresponding life stages of the two other species. The developmental threshold of all life stages was highest for O. duftschmidi. For the three life stages of each species, a linear model was found satisfactory to describe the developmental rate - temperature relationship. In genera!, the stage-specific mortality is highest in O. duftschmidi life stages. On the larval and pupal stages, O. duftschmidi responds with increasing, and the other two species with decreasing mortality rates to a temperature increase from 20 to 25°C.